A canonical narrative of popular music: 100 years after Robert Lehmann-Nitsche recordings. (Revista Argentina de Musicología, 2018)
The earliest large collection of aboriginal and popular music in Argentina was carried out by Robert Lehmann-Nitsche between 1905 and 1909. The German researcher was convinced that he was dealing with very exotic musical expressions, which were threatened by urbanization and industrialization processes. Consequently he recorded 242 wax cylinders, currently part of the collection of the Phonogramm-Archiv in Berlín. His reified perspective. that defined musical expressions as if they were storable objects. influenced the musical studies made by local researchers who came after him. The critical observation of his method may throw light on to what extent his epistemology had an influence on the local canon, leading many later researches, consciously or unconsciously, to follow the same premises Lehmann-Nitsche applied.
Keywords: Robert Lehmann-Nietsche